7z-12+18z+8=4-4(5-6z+z)

Simple and best practice solution for 7z-12+18z+8=4-4(5-6z+z) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7z-12+18z+8=4-4(5-6z+z) equation:


Simplifying
7z + -12 + 18z + 8 = 4 + -4(5 + -6z + z)

Reorder the terms:
-12 + 8 + 7z + 18z = 4 + -4(5 + -6z + z)

Combine like terms: -12 + 8 = -4
-4 + 7z + 18z = 4 + -4(5 + -6z + z)

Combine like terms: 7z + 18z = 25z
-4 + 25z = 4 + -4(5 + -6z + z)

Combine like terms: -6z + z = -5z
-4 + 25z = 4 + -4(5 + -5z)
-4 + 25z = 4 + (5 * -4 + -5z * -4)
-4 + 25z = 4 + (-20 + 20z)

Combine like terms: 4 + -20 = -16
-4 + 25z = -16 + 20z

Solving
-4 + 25z = -16 + 20z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-20z' to each side of the equation.
-4 + 25z + -20z = -16 + 20z + -20z

Combine like terms: 25z + -20z = 5z
-4 + 5z = -16 + 20z + -20z

Combine like terms: 20z + -20z = 0
-4 + 5z = -16 + 0
-4 + 5z = -16

Add '4' to each side of the equation.
-4 + 4 + 5z = -16 + 4

Combine like terms: -4 + 4 = 0
0 + 5z = -16 + 4
5z = -16 + 4

Combine like terms: -16 + 4 = -12
5z = -12

Divide each side by '5'.
z = -2.4

Simplifying
z = -2.4

See similar equations:

| 10y-8y-y=16 | | 4-2(x-4)=-3(4x-4) | | 6v-7(1+4v)=-183 | | 10b-10b+2b+b-b=16 | | x^3-x^2y-xy+y^2=0 | | 5y-2y+2y-2y=18 | | 94.6=32.6-T | | 2x/3=-14 | | 16c-13c=15 | | 8m-2m=18 | | -2x-y+2z=1 | | 8a-7a=9 | | Ln(sqrt)x+8=1 | | -x-y+2z=1 | | x+2y-2z=5 | | 14g+6g=20 | | 2a-6b-c=1 | | 17+5z=7 | | 3a+5b+c=-4 | | 10w-8w=8 | | a+3b-2c=7 | | -9.3=B-3.4 | | x^3-x^2y-4x+y^3+xy^2-4y=0 | | y-2z=-2 | | 13d-5d=16 | | -35=5y+5 | | x-y+3z=30 | | x^3-x^2y+xy^2+y^3-4x-4y=0 | | 2.15x=x+250 | | -(4XY-8)+2(4XY+6)= | | 2.5x=x+250 | | -2.9=F+3.8 |

Equations solver categories